2002
DOI: 10.1097/00042192-200201000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transdermal estradiol in the regulation of leptin levels of postmenopausal women: a double-blind, placebo-controlled study

Abstract: Low doses of transdermal estradiol exert no influence on fasting leptin levels or BMI. The possibility that different doses of estradiol exert a more pronounced effect on circulating leptin needs to be addressed in comparative studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Our study is different from previous reports in that the men reported here had previously undergone a prolonged period of androgen deprivation and at baseline were hypogonadal, presumably with the detrimental effects on body composition (increased percent body fat as a result of increased fat mass and loss of lean mass) already present. These data support the hypothesis that estrogen is unlikely to directly affect leptin secretion and are in agreement with previous studies in women demonstrating that hormonal replacement therapy is not significantly related to leptin levels (54,55).…”
Section: Discussionsupporting
confidence: 92%
“…Our study is different from previous reports in that the men reported here had previously undergone a prolonged period of androgen deprivation and at baseline were hypogonadal, presumably with the detrimental effects on body composition (increased percent body fat as a result of increased fat mass and loss of lean mass) already present. These data support the hypothesis that estrogen is unlikely to directly affect leptin secretion and are in agreement with previous studies in women demonstrating that hormonal replacement therapy is not significantly related to leptin levels (54,55).…”
Section: Discussionsupporting
confidence: 92%
“…The results of many other studies, however, demonstrated no variation (7,13,32,(41)(42)(43)(44)(45) or even decreased (10,28,46,47) serum leptin levels with HT. Heterogeneity of the studied populations with respect to race, body composition, age, time since menopause, and indications for HT are the main factors that may explain the discrepancy of the results from various studies.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, after menopause, there is an increase in body weight, BMI, and fat mass, with a centralization of fat distribution. Thus, from a theoretical point of view, administration of HT may stop these changes and even restore a premenopausal pattern, explaining the decreased (26) or unaffected (30,35,37) leptin levels found in some studies. On the contrary, our data suggest an increasing effect on leptin levels with all schedules, doses, and routes of HT and corroborate data from previous small, short-term studies (31,34).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, data on the effect of HT on serum leptin are highly discordant. Hormone therapy after menopause has been reported to result in unmodified, increased, or decreased leptin levels (26,(30)(31)(32)(33)(34)(35). The dosage and mode or route of HT administration, and/or the addition of a progestin might explain the discrepancy in results.…”
Section: Discussionmentioning
confidence: 99%